Synchronization versus staggering of price changes in Brazil - Nunes, Evelyn Monteiro Pereira (2010)
While several models assume that price changes are staggered over time, both theory and empirical evidence are ambiguous. This work attempts to identify the behavior of price setters by analyzing a large Brazilian data set. It is found an evidence of staggering, but the more aggregated the data are, the closer the price changes are to perfect synchronization. The Brazilian economy also presents a heterogeneous frequency and synchronization of price adjustments among product categories, which also vary with the inflation rate.